Advances and applications of chemical protective clothing system. (July 2019) - Bhuiyan, M A Rahman; Wang, Lijing; Shaid, Abu; Shanks, Robert A; Ding, Jie
Protection is obligatory for the safety of people in certain occupations where they might be exposed to hazardous chemicals. This review provides an overview of chemical protective clothing, along with its necessity during industrial and military operations as well as in response to acts of terror. Moreover, chemical protective or barrier suits are illustrated and explained including their types, selection processes based on chemical hazards, working environments, and various materials available for the fabrication of effective barrier clothing. Additionally, this review elucidates current research gaps, while underscoring the challenges facing recently developed chemical protective clothing, by compiling relevant research onto a single platform. Besides, this review includes and delineates future trends in chemical protective outfits based on electro-spun nano-fibre technology involved in both detection and decomposition of poisonous chemical agents that come in contact with clothing material, and the integration of selectively permeable membrane technology to discriminately block hazardous chemicals.